2013
DOI: 10.1158/1541-7786.mcr-12-0649
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Epigenomic Cross-talks in the Regulatory Landscape of miRNAs in Breast Cancer

Abstract: MicroRNAs (miRNA) are a class of endogenous, small noncoding RNAs found in animals, plants, and viruses that control their target gene expression posttranscriptionally. They are involved in a wide array of biological processes including cell differentiation, development, cell death and homeostasis, and fine-tune the regulation of these pathways. Their aberrant expressions have been associated with different diseases. These small RNAs are also known to function as oncogenes, oncosupressor genes, modulators of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 151 publications
(111 reference statements)
0
39
0
7
Order By: Relevance
“…and modulation of transcription factors (e.g., TP53 and TP63) has also started to emerge, creating a controlled feedback mechanism. 19,28,[76][77][78]85 The miR-29 family was shown to directly target DNMT3A and DNMT3B and indirectly target DNMT1 through regulation of the transactivator SP1 or RBL2, [86][87][88] while miR-148 and miR-140 were shown to target DNMT1 and DNMT3B. [89][90][91] miR-101 was shown to regulate the expression of EZH2, catalytic subunit of the polycomb repressive complex 2, which mediates epigenetic gene silencing by trimethylating histone H3 lysine 27.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and modulation of transcription factors (e.g., TP53 and TP63) has also started to emerge, creating a controlled feedback mechanism. 19,28,[76][77][78]85 The miR-29 family was shown to directly target DNMT3A and DNMT3B and indirectly target DNMT1 through regulation of the transactivator SP1 or RBL2, [86][87][88] while miR-148 and miR-140 were shown to target DNMT1 and DNMT3B. [89][90][91] miR-101 was shown to regulate the expression of EZH2, catalytic subunit of the polycomb repressive complex 2, which mediates epigenetic gene silencing by trimethylating histone H3 lysine 27.…”
Section: Discussionmentioning
confidence: 99%
“…97 Once it was widely demonstrated that an aberrant microRNAome is a hallmark in cancer, accumulating evidence showed that the microRNA expression is affected by the same epigenetic mechanisms as mRNA transcription. 29,74,83,85 microRNA expression can be regulated by several epigenetic mechanisms, including transcriptional modulation of microRNA genes by transcription factors, promoter methylation, or histone acetylation, and/or altered microRNA maturation. 83,85 The ability of microRNAs to regulate the components of the epigenetic machinery, targeting molecules involved in the DNA methylation, histone acetylation, and modulation of transcription factors is also started to emerge creating a controlled feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Из них 136 miR произошли от некодирующих РНК-последова-тельностей (другие), которые также с наибольшей вероятностью произошли из нехарактерных SINE-элементов [19]. Учитывая важную роль микроРНК в метилировании генома [4] и регуляции модифика-ции гистонов в онтогенезе человека, можно пред-положить, что ТЕ являются материальной основой эпигенетической наследственности.…”
Section: транспозоны как материальная основа эпи-генетической наследсunclassified
“…1). Данные эпи-микроРНК косвенно влияют на экс-прессию генов онкосупрессоров, чья экспрессия контролируется эпигенетическими факторами [4]. Все больше фактов указывает на большое значение дерегуляции микроРНК в инициации и прогресси-ровании опухолей, при котором они могут вести себя в роли онкогенов или онкосупрессоров в зави-симости от клеточной функции их мишеней.…”
Section: Introductionunclassified